Hyper-reflective Spots in OCT Imaging in Retinal Diseases: Imaging Features and Clinico-pathologic Correlation - Ahmed Darwish (New Advances in Medicine and Medical Science Vol. 1, 2023)
New potential biomarkers for retinal disease with an important impact on diagnosis, prognosis and management are recently available and continuously discovered because of the rapid advances in the technology of optical coherence tomography. One of those biomarkers are the hyper-reflective spots that were found in a broad spectrum of retinal diseases particularly diabetic macular edema and age related macular degeneration and others. Detecting those HRSs is crucial in the management strategies of those diseases as high lightened in this chapter.